GROWTH MODELS FOR Araucaria angustifolia (BERTOL.) KUNTZE IN DIFFERENT ECOLOGICAL GRADIENTS IN THE STATE OF SANTA CATARINA - Ricken, Pollyni; Póvoa de Mattos, Patrícia; Muñoz Braz, Evaldo; Hess, André Felipe; Yoshihiro Nakajima, Nelson; Tuyoshi Hosokawa, Roberto (Floresta, 2022)
The growth of one or more individuals in a forest is variable with the biotic and abiotic conditions of the environment. Therefore, the objective of this article was to obtain the age and growth estimates of Araucaria angustifolia, in different altitude gradients of occurrence of the species, and to identify the culmination points in the basal area. The study covered three areas with Araucaria Forest in Santa Catarina state, considering different altitudes of occurrence of the species. Non-destructive samples were collected from 226 trees, 76, 73 and 77 trees in areas 1, 2 and 3, respectively. Using the time series, diametric growth models were adjusted, allowing to obtain the curves of current annual increment and average annual increment. In area 1, the age range of the samples was 174 years, in area 2, it was 170 years and in area 3, it was 42 years. The average annual increment for areas 1, 2 and 3 were 0.33 cm, 0.51 cm and 1.01 cm, respectively. Araucaria manages to reach a high growth potential when it is in better development conditions (soil, nutrients, light…). Keywords: Araucaria forest. Dendrochronology. Altitude.